Determination of clay mineral aspect ratios from conductometric titrations. (March 2014) - Weber, C.; Heuser, M.; Mertens, G.; Stanjek, H.
Abstract: It has been established that disagreements between different methods of particle size determination of clay minerals can be ascribed to the non-spherical shape of the clay particles. However, by having aspect ratios available, particle sizes can be harmonized. One frequently used approach to obtain aspect ratios is to compare particle sizes originating from at least two devices operating on the basis of different physical principles. In this contribution aspect ratios of nine kaolinite-dominated and one dickite-dominated sample were determined by conductometric titrations. The aspect ratios obtained were then successfully used to correlate particle size distributions from dynamic laser scattering and acoustic spectroscopy.